Simultaneous Modeling of Biomarker and Toxicity Response Predicted Optimal Regimen of Guadecitabine (SGI‐110) in Myeloid Malignancies. (28th September 2017) - Xu, Cong; Goggin, Timothy K.; Su, Xiang‐Yao; Taverna, Pietro; Oganesian, Aram; Lowder, James N.; Azab, Mohammad; Kantarjian, Hagop
Abstract : Guadecitabine (SGI‐110) is a novel next‐generation hypomethylating agent (HMA) administered as s.c. injection with extended decitabine exposure. Dose/exposure‐response analyses of longitudinal measures of long interspersed nucleotide element‐1 (LINE‐1) methylation and absolute neutrophil counts (ANC) pooled from 79 and 369 patients in 2 phase I/II trials, respectively, were performed to assist, through modeling and simulation, the selection of dosing regimens for phase III. Simulation of ANC predicted a decrease after a 5‐day regimen of 60 mg/m 2 with partial recovery before the next cycle, whereas the nadir of 90 mg/m 2 on the same schedule was below 100/µl. ANC following a 60 mg/m 2 10‐day regimen was predicted to be suppressed below 100/µl as long as treatment continued without recovery. The developed models provided useful tools to assist simultaneous evaluation of the relative dynamics of the two effects (DNA demethylation and the effect on ANC).